The Influence of Work Environment on Employees' Work Productivity with Motivation as an Intervening Variable at PT. Tirta Sari Surya Indragiri Hulu District - Yenny Iskandar; Afriaris, Said; Astarman (MultiTech Publisher, 2023)
The reduced growth in employee productivity levels can cause various problems such as low levels of profits for the company. Therefore, productivity is very important to pay attention to. Apart from that, the importance of this is also because a high level of productivity will be able to strengthen the country's economy which will then have an impact on increasing the standard of living, improving the quality of life in other words. Productivity can be said to be a measure that shows the consideration between input and output issued by the Company and the role of labor per unit of time, or in other words, measuring efficiency requires identifying performance results.